Change Detection on SAR data using PCA Algorithm - Srivastava, Saurabh; Kumar, Vijay; Gupta, Rahul; Kaur, Supreet (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In this paper, we proposed an approach for unsupervised change detection technique on SAR data. Change detection is process of automatically identifying and analyzing the regions which undergone some changes such as spatial or spectral changes. As various techniques are available to change detection but are used for general satellite images. In order to detect change on SAR images we use PCA technique which detect the change by finding the different pixel using threshold level and compare with earlier image one.